Stability parameters in bottle gourd (Indian Journal of Arid Horticulture, 2025)
The investigation was carried out to study the stability parameters for fruit yield and associated characters in bottle gourd. The material comprised of nine parents, 36 F, hybrids and one standard check. The environments were created by sowing the crop on the different dates at two different locations. The study revaled the presence of genotypes x environment interactions. The variance due to G x E (linear) was significant for all the traits indicating that major portion of G x E interaction were linear in nature and prediction of these traits was still possible. Based on the individual genotypes of adaptability, it is evident that three parental line and twelve hybrids recorded high mean performance alongwith non-significant deviation from regression. The hybrid Banswara Loca-1 x PSPL recorded below average regression coefficient (bi
Keywords: Stability; bottle gourd; genotypes x environment and hybrids